Path Analysis of Sociodemography Determinants, Sexual Behavior, and HIV Status in Sragen, Central Java - Fiqih Agustyna Murti; Argyo Dermatoto; Bhisma Murti (Journal of Health Promotion and Behavior, 2020)
Background: HIV/ AIDS is a global problem, including Indonesia. HIV/ AIDS sufferers in Sragen Regency have increased every year. Sociodemographic factors and the many places as hosts for sexual behavior are the causes of HIV cases that cannot be suppressed. The purpose of this study was to determine the determinants of sociodemography, sexual behavior and HIV status.Subjects and Method: This was a cross sectional study conducted in Sragen Regency, Central Java, from August to December 2018. The sample consisted of 200 residents who did VCT. The sampling technique chosen was fixed disease sampling. The dependent was HIV status. The independent variables were occupation, knowledge of sexual partner HIV status, social support, sexual behavior and locus of control. Data were collected using a questionnaire and analyzed using path analysis.Results: HIV risk increased directly with risky work (b= 7.5; 95% CI= 0.79 - 1.42; p= 0.029), risky sexual behavior (b= 0.48; 95% CI= -0.63 - 1.73; p = 0.405 ), and sexual partners who did not know the HIV status of their sexual partners (b= 0.48; 95% CI= -0.63 to 1.73; p= 0.405). HIV risk is indirectly influenced by locus of control, social support, occupation, and sexual partners who do not know the HIV status of their sexual partners through sexual behavior.Conclusion: HIV status is directly influenced by occupation, sexual behavior and knowledge of sexual partners' HIV status, as well as indirectly by locus of control, social support, occupation and knowledge of sexual partners HIV status through sexual behavior.Keywords: HIV, sociodemographic, sexual behaviorCorrespondence: Fiqih Agustyna Murti. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: murti.fiqih@gmail.com. Mobile: +6285729752541.Journal of Health Promotion and Behavior (2020), 05(04): 240-247https://doi.org/10.26911/thejhpb.2020.05.04.02.